Tip-growth of aligned carbon nanotubes on cobalt catalyst supported by alumina using alcohol catalytic chemical vapor deposition - Bistamam, Mohd Shahril Amin; Mohd Abid, Mohd Asyadi Azam (Elsevier, 2014)
Metal oxide layer helps to support carbon nanotubes (CNTs) aligned perpendicular as well as preventing the tip-growth take place due to the strong adhesion force between the catalyst and metal oxide. However, in this work we discovered tip-growth of aligned CNTs with Co as catalyst on thermally oxidized Al/SiO2/Si substrate system using simple alcohol catalytic chemical vapor deposition technique.